“Fostering Creativity in Visual Arts Lessons for Grades 5–7 Using Gamification Techniques” - Axmedov Dilmurod Xolmamatovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the application of gamification techniques in visual arts lessons for grades 5–7 to foster creativity, engagement, and problem-solving skills. The study shows that incorporating game elements such as challenges, rewards, and competitions motivates students to actively participate in artistic tasks, enhances their creative thinking, and encourages collaborative learning. Gamification provides an innovative approach to making art education interactive, engaging, and effective in developing students’ artistic competencies.